2010
DOI: 10.1080/10826071003766237
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF TEMPERATURE ON THE NEUTRAL LIPID CONTENT OF BIOMPHALARIA GLABRATA AS DETERMINED BY HIGH PERFORMANCE THIN LAYER CHROMATOGRAPHY-DENSITOMETRY AND OBSERVATIONS ON SNAIL FECUNDITY

Abstract: & High performance thin-layer chromatography with densitometry was used to examine the effects of extreme temperature on the neutral lipid content of Biomphalaria glabrata, and observations on fecundity were made at these extreme temperatures of 32, 28, and 14 C. Fecundity results showed that egg laying at 32 C was higher than at 28 and 14 C. Free sterols, free fatty acids, and triacylglycerols were quantified at 2 and 4 weeks after the initiation of the experiment using Analtech channeled high performance sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Glycerophospholipids (mainly phosphatidylethanolamine and phosphatidylcholine) are important components of cell membranes (Nguyen et al, 2020;Overgaard et al, 2008), and have close relations with the permeability of the cell membrane and the activity of ATPases (Nemova et al, 2017). The regulation of glycerophospholipid content under thermal stress may be an adaptive response to warmer temperature (Bolstridge et al, 2010;Hunsberger et al, 2014). In the present study, the levels of GPE and CDP-EA generated by diethanolamine in glycerophospholipid metabolism increased.…”
Section: Glycerophospholipid Metabolism and Cell Membrane Stabilizationsupporting
confidence: 47%
“…Glycerophospholipids (mainly phosphatidylethanolamine and phosphatidylcholine) are important components of cell membranes (Nguyen et al, 2020;Overgaard et al, 2008), and have close relations with the permeability of the cell membrane and the activity of ATPases (Nemova et al, 2017). The regulation of glycerophospholipid content under thermal stress may be an adaptive response to warmer temperature (Bolstridge et al, 2010;Hunsberger et al, 2014). In the present study, the levels of GPE and CDP-EA generated by diethanolamine in glycerophospholipid metabolism increased.…”
Section: Glycerophospholipid Metabolism and Cell Membrane Stabilizationsupporting
confidence: 47%
“…Glycerophospholipids (mainly phosphatidylethanolamine and phosphatidylcholine) are important components of cell membranes [52,53] and are closely related to cell membrane permeability and ATPase activity [54]. Regulation of glycerophospholipid content under heat stress may be an adaptive response to elevated temperature [55,56]. Serine, a modification group in the synthesis of phosphatidylserine (PtdSer), is an essential membrane phospholipid that can regulate the function and state of proteins in membranes and plays a vital role in cell metabolism [57].…”
Section: Heat Stress Alters Gut Microbiota-related Metabolitesmentioning
confidence: 99%
“…Bolstridge et al [11] examined the effects of extreme temperature on the neutral lipid content of B. glabrata, and observations on fecundity were made at these extreme temperatures of 32 °C, 28 °C, and 14 °C. Fecundity results showed that egg laying at 32 °C was higher than in the lower temperature groups.…”
Section: Literature Reviewmentioning
confidence: 99%